Implementation of Multi-literacy Education Based on Cultural Literacy with the TANDUR Strategy in Community Learning Center (CLC) (Edukasi, 2022)
The need for a grand design of education in the implementation of literacy education so that it can provide an output in the form of a society that is literate and able to solve problems in their lives as expected by the law. No. 20 of 2003 article 3 which states that national education functions to develop abilities and shape national character and civilization so that they are able to actively participate in advancing the world community. So, to be able to make it happen, the TANDUR strategy is a strategy solution for implementing literacy education. Development The implementation of multi-literacy education at PKBM is carried out using the RnD method and the application of quasi-experiments to test the developed model. The results obtained in this study are that the TANDUR strategy applied in implementing multi-literacy at PKBM has a positive effect, both on tutors, the learning process, and the learning community. So it is hoped that with the TANDUR strategy it can be implemented and socialized to education units that will organize multi-literacy education.